Teaching and development of Filipino nationalism using the inquiry approach at the college level - Luis, Consuelo Panganiban 1948- (1977)
Inquiry is offered as the very core of the "new Social Studies". The writer was inspired to write on this strategy due to the fact that Philippine History contains issues that are controversial. The final portion of this study presented recommendations pointing to the need for thorough practice on inquiry teaching and stressing the important role of the teacher in the development and use of inquiry approach as a strategy in teaching.
"December, 1977."
Vita.
Thesis (M.A.T. Social Studies)--University of the Philippines, Diliman.
Keywords: Nationalism -- Study and teaching (Higher) -- Philippines